The Creativity of Early Childhood Painting through Media Waste in Islamic Center Kindergarten Brebes - Firasaty, Okda; Astuti, Henny Puji (BELIA: Early Childhood Education Papers, 2017)
The development of childrens creativity is an important activity in order to develop the potential of children from an early age because, at this time the potential of childrens creativity is at the peak of development to be sharpened and directed. The creative potential is very important for the development of children it is a creativity of the children in painting. Usually people will use conventional media to paint such as paintbrush, liquid dye and canvas but, as the time progressed painting can use an unconventional media that is waste. the painting technique used id mosaic technique. Problem in this research is whether there is difference of creativity of painting using waste media for early age children. This research aimed to know the  differences of creativity of painting using waste media for early age children. The method used to collect data is by quantitative approach with the research subjects of children aged 5-6 years who are in class B1 and B2 Islamic Centre Kindergarten Brebes. The data collection technique in this research using painting creativity scale of early age children, while the data analysis using independent t-Test sample. The result of this research based on statistics, obtained the mean value 94,75 for experiment group and 86,13 for control group. The result of the research stated that there is a differences of creativity of painting through waste media. The creativity of painting through waste media is higher than without waste media with experimental group mean values of  94,75 and 86,13 for the control group.